2020
DOI: 10.1155/2020/7403152
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related ESBL-Producing Leclercia adecarboxylata Septicemia in Hemodialysis Patient: An Emerging Pathogen?

Abstract: We report a multidrug-resistant strain of Leclercia adecarboxylata which was responsible for a catheter-related bacteremia, in a 50-year-old female with an end-stage renal disease on hemodialysis. The isolated strain was an extended beta-lactamase producer. Based on a literature review of L. adecarboxylata, there have been only two reports of extended beta-lactamase producer strains. To our knowledge, this is the first case reported in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In our study, a recent exposition to an aquatic environment was identified in one patient (professional swimmer presenting with corneal abscess with keratitis), such as few cases in medical literature [9]. Until now, this bacterium was considered a low-virulence pathogen with uncertain pathogenicity in human infections [6,9,10]. In our 8 samples, L. adecarboxylata was considered as a clinically significant pathogen based on clinical presentations, except for 2 episodes (one patient with VAP and the second with UTI) when clinicians considered it as an asymptomatic carriage or colonization and they have been mistreated.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, a recent exposition to an aquatic environment was identified in one patient (professional swimmer presenting with corneal abscess with keratitis), such as few cases in medical literature [9]. Until now, this bacterium was considered a low-virulence pathogen with uncertain pathogenicity in human infections [6,9,10]. In our 8 samples, L. adecarboxylata was considered as a clinically significant pathogen based on clinical presentations, except for 2 episodes (one patient with VAP and the second with UTI) when clinicians considered it as an asymptomatic carriage or colonization and they have been mistreated.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly to other published reports, the overwhelming majority of isolates were susceptible to tested antibiotics in both mentioned studies. Nevertheless, ESBL or AmpCproducing isolates, resistant isolates to cefotaxime, ceftazidime and cefepime were described, in addition to an blaNDM-1-producing strain isolated from a male patient, suffering an open ankle fracture and crush injury to his left foot [31,32]. Comparably to other Gram-negative gut bacteria, the emergence and spread of multidrug-resistant strains is to expected [33].…”
Section: Discussionmentioning
confidence: 99%
“…First discovered in 1962 as “Escherichia Adecarboxylata (E.coli),” this pathogen was described as a motile, gram-negative, oxidase-negative bacterium that shared many similar biochemical properties with Escherichia Coli [ 2 ]. Due to advancement in microbiology identification capabilities, there have been an increasing number of L. adecarboxylata infections diagnosed, primarily as an opportunistic pathogen.…”
Section: Discussionmentioning
confidence: 99%